Bisphenol M cyanate ester and preparation method thereof
By combining bisphenol M cyanate resin with thermosetting resin, modified hydrotalcite, etc., the problem of poor toughness of cyanate resin is solved, and the effect of significantly improving mechanical properties while maintaining excellent dielectric and heat resistance is achieved.
Patent Information
- Application Number
- CN202411619207.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-07
AI Technical Summary
The toughness of cyanate resin is poor, making it difficult to toughen while maintaining its original excellent dielectric properties, heat resistance and moisture resistance.
Bisphenol M cyanate resin was used to react with thermosetting resin, modified hydrotalcite, catalyst and promoter to prepare a bisphenol M cyanate resin with excellent mechanical properties, dielectric properties and heat resistance.
It significantly improves the mechanical properties and dielectric properties of cyanate resin, while maintaining its original heat and moisture resistance, and is suitable for use in areas with high toughness requirements.
Smart Images

Figure BDA0005133021320000081 
Figure BDA0005133021320000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cyanate resins, and particularly relates to bisphenol M cyanate and a preparation method thereof. Background Art
[0002] Cyanate esters (CE) are recognized as the most competitive resin type for the preparation of structural-functional materials due to their excellent dielectric properties, outstanding heat resistance, and good comprehensive mechanical properties. They show great application prospects in cutting-edge fields such as electronics, communications, and aerospace. Cyanate esters are phenolic derivatives containing two or more cyanate functional groups. Under the action of heat and catalysts, cyanate esters undergo cyclotrimerization reactions to form a highly cross-linked network structure containing triazine rings. They are low-dielectric, low-loss resin matrix materials.
[0003] With the rapid development of industry, higher and more performance requirements have been put forward for cyanate ester resins, which are mainly reflected in outstanding thermal stability, better dielectric properties, better toughness, lower water absorption, and better molding processability. In order to improve the dielectric properties of materials, cyanate esters are usually compounded with hollow quartz fibers, aramid fibers, PBO fibers, high-density polyethylene fibers or mixed hybrid fibers. Although the dielectric properties have been improved, there are a series of problems such as low comprehensive strength of the material, easy increase in dielectric constant at high temperature, and weak interface bonding characteristics of mixed fibers. In order to solve the problem that the curing temperature is too high and will damage the interface effect between cyanate ester and fiber, the curing temperature of the resin is also reduced by adding transition metal catalysts, but it will cause the dielectric properties and heat resistance of the composite material to decrease, making it difficult to meet the application requirements of the new generation of antenna technology in terms of comprehensive material performance. Cyanate ester resin is a thermosetting resin. Like other thermosetting resins, CE resin also has the problem of high brittleness. The high brittleness restricts the application of cyanate ester resin in the field of high toughness requirements to a certain extent.
[0004] At present, there are many studies on improving the toughness of cyanate ester resins, mainly through copolymerization / blending with thermoplastic resins, rubber, other thermosetting resins, and inorganic rigid particles. These methods have a common problem: it is difficult to toughen the cyanate ester resin while maintaining its original excellent properties such as dielectric properties, heat resistance, and moisture resistance; at the same time, it may also bring about new problems such as poor processability. Therefore, it is of great significance and application value to develop a cyanate ester that can improve the toughness of cyanate ester while retaining its original excellent properties. Summary of the invention
[0005] In order to solve the problem of poor toughness of cyanate resin, the present invention provides a bisphenol M cyanate and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A bisphenol M cyanate ester, comprising the following raw materials in parts by weight:
[0008] Bisphenol M cyanate resin monomer: 100 parts;
[0009] Thermosetting resin: 15-20 parts;
[0010] Modified hydrotalcite: 3-8 parts;
[0011] Catalyst: 0.03-0.05 parts;
[0012] Accelerator: 0.1-0.15 parts.
[0013] As a further solution of the present invention, the preparation steps of the modified hydrotalcite are as follows:
[0014] POSS (polyhedral oligomeric silsesquioxane) is added to tetrahydrofuran, stirred, hydrotalcite is added, ultrasonic dispersion is performed for 1-1.5 hours, the temperature is controlled at 75-80°C, under nitrogen atmosphere, reflux reaction is performed for 12-14 hours, after the reaction is completed, the reaction is cooled to room temperature, filtered, washed and dried to obtain modified hydrotalcite. POSS is used to chemically react with hydrotalcite, and POSS is introduced into the surface and interlayer of hydrotalcite, which improves the dispersion performance and compatibility of hydrotalcite in the matrix resin, and then added to the raw materials, which can significantly improve the mechanical properties and dielectric properties of cyanate resin.
[0015] As a further embodiment of the present invention, the usage ratio of POSS, tetrahydrofuran and hydrotalcite is 0.50-0.55 g:100 mL:0.10-0.12 g.
[0016] As a further embodiment of the present invention, the particle size of the hydrotalcite is 30-60 μm.
[0017] As a further solution of the present invention, the thermosetting resin is at least one of epoxy resin (EP), bismaleimide resin (BMI), and benzoxazine resin (BOZ). The addition and mixing of the thermosetting resin can effectively reduce the crosslinking density of the cured product, generate some toughness groups, obtain cured products with different branching degrees and micro-network structures, and thus improve the mechanical properties of the material, while slightly improving the heat resistance of the cured product, and significantly reducing the shrinkage rate and moisture absorption rate.
[0018] As a further embodiment of the present invention, the catalyst is at least one of octanoic acid metal salt, acetylacetonate metal salt, and dibutyl dilaurate metal salt.
[0019] As a further embodiment of the present invention, the accelerator is one of nonylphenol, phenol, resorcinol and o-cresol.
[0020] The present invention also provides a method for preparing bisphenol M cyanate, comprising the following steps:
[0021] S1, weighing by weight, adding the catalyst to the accelerator, and dispersing by high-speed shearing to obtain a dispersion;
[0022] S2, heating and stirring the bisphenol M cyanate monomer, the thermosetting resin and the modified hydrotalcite to obtain a bisphenol M cyanate prepolymer;
[0023] S3, adding the dispersion in step S1 to the bisphenol M cyanate prepolymer, stirring and reacting to obtain bisphenol M cyanate resin.
[0024] As a further embodiment of the present invention, the stirring reaction temperature in S2 is 150-200° C., and the stirring reaction time is 8-10 h.
[0025] As a further solution of the present invention, the stirring reaction temperature in S3 is 80-85° C., and the stirring reaction time is 0.5-1 h.
[0026] Beneficial effects of the present invention:
[0027] In the present invention, an appropriate amount of catalyst, promoter, thermosetting resin and modified hydrotalcite are reacted with bisphenol M cyanate resin monomer to prepare bisphenol M cyanate resin with excellent dielectric properties, hygroscopic properties, thermomechanical properties and mechanical properties. Wherein the hydrotalcite after POSS surface modification is better dispersed in the composite material, when the material is impacted, there are more dispersed particles to disperse stress, thereby improving impact strength, thereby avoiding the phenomenon such as composite material is prone to cracking. In addition, the amino group on the POSS molecular structure grafted on the hydrotalcite surface and the hydroxyl on the hydrotalcite surface can form a bond with the cyano group of the bisphenol M cyanate resin monomer, and the hydrotalcite has a binding effect on the bisphenol M cyanate resin, which can limit the movement and deformation of the bisphenol M cyanate resin.
[0028] The bisphenol M cyanate ester resin prepared by the invention has excellent mechanical properties, good heat resistance, low moisture absorption rate and stable size. Meanwhile, the preparation method provided has simple process, easy controllable parameters and low cost, and is suitable for large-scale industrial production. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides a modified hydrotalcite, and the preparation steps are as follows:
[0032] 0.50 g of POSS was added to 100 mL of tetrahydrofuran, stirred, and 0.10 g of hydrotalcite (35 μm) was added. The mixture was ultrasonically dispersed for 1 h. The temperature was controlled at 80 ° C. Under nitrogen atmosphere, the mixture was refluxed for 12 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed, and dried to obtain modified hydrotalcite.
[0033] Example 2
[0034] This embodiment provides a modified hydrotalcite, and the preparation steps are as follows:
[0035] 0.55 g of POSS was added to 100 mL of tetrahydrofuran, stirred, and 0.12 g of hydrotalcite (55 μm) was added. The mixture was ultrasonically dispersed for 1 h. The temperature was controlled at 80 °C and refluxed for 14 h under nitrogen atmosphere. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed and dried to obtain modified hydrotalcite.
[0036] Example 3
[0037] This embodiment provides a bisphenol M cyanate ester, including the following raw materials in parts by weight:
[0038] Bisphenol M cyanate resin monomer: 100 parts, epoxy resin: 15 parts, modified hydrotalcite in Example 1: 3 parts, copper acetylacetonate: 0.03 parts, nonylphenol: 0.1 parts.
[0039] The preparation method is as follows:
[0040] S1. Weigh copper acetylacetonate in parts by weight and add it to nonylphenol, and disperse it by high-speed shearing to obtain a dispersion;
[0041] S2, heating and stirring the bisphenol M cyanate monomer, epoxy resin and the modified hydrotalcite in Example 1, and stirring and reacting at 150° C. for 10 hours to obtain a bisphenol M cyanate prepolymer;
[0042] S3, adding the dispersion in step S1 to the bisphenol M cyanate prepolymer, stirring and reacting at 85° C. for 0.5 h to obtain bisphenol M cyanate resin.
[0043] Example 4
[0044] This embodiment provides a bisphenol M cyanate ester, including the following raw materials in parts by weight:
[0045] Bisphenol M cyanate resin monomer: 100 parts, epoxy resin: 15 parts, modified hydrotalcite in Example 1: 5 parts, copper acetylacetonate: 0.03 parts, nonylphenol: 0.1 parts.
[0046] The preparation method is as follows:
[0047] S1. Weigh copper acetylacetonate in parts by weight and add it to nonylphenol, and disperse it by high-speed shearing to obtain a dispersion;
[0048] S2, heating and stirring the bisphenol M cyanate monomer, epoxy resin and the modified hydrotalcite in Example 2, and stirring and reacting at 150° C. for 10 hours to obtain a bisphenol M cyanate prepolymer;
[0049] S3, adding the dispersion in step S1 to the bisphenol M cyanate prepolymer, stirring and reacting at 85° C. for 0.5 h to obtain bisphenol M cyanate resin.
[0050] Example 5
[0051] This embodiment provides a bisphenol M cyanate ester, including the following raw materials in parts by weight:
[0052] Bisphenol M cyanate resin monomer: 100 parts, epoxy resin: 15 parts, modified hydrotalcite in Example 1: 8 parts, copper acetylacetonate: 0.03 parts, nonylphenol: 0.1 parts.
[0053] The preparation method is as follows:
[0054] S1. Weigh copper acetylacetonate in parts by weight and add it to nonylphenol, and disperse it by high-speed shearing to obtain a dispersion;
[0055] S2, heating and stirring the bisphenol M cyanate monomer, epoxy resin and the modified hydrotalcite in Example 1, and stirring and reacting at 150° C. for 10 hours to obtain a bisphenol M cyanate prepolymer;
[0056] S3, adding the dispersion in step S1 to the bisphenol M cyanate prepolymer, stirring and reacting at 85° C. for 0.5 h to obtain bisphenol M cyanate resin.
[0057] Example 6
[0058] This embodiment provides a bisphenol M cyanate ester, including the following raw materials in parts by weight:
[0059] Bisphenol M cyanate resin monomer: 100 parts, epoxy resin: 20 parts, modified hydrotalcite in Example 2: 7 parts, dibutyl copper dilaurate: 0.04 parts, nonylphenol: 0.12 parts.
[0060] The preparation method is as follows:
[0061] S1. Weigh dibutyl copper dilaurate in parts by weight and add it to nonylphenol, and disperse it by high-speed shearing to obtain a dispersion;
[0062] S2, heating and stirring the bisphenol M cyanate monomer, epoxy resin and the modified hydrotalcite in Example 2, and stirring and reacting at 150° C. for 10 hours to obtain a bisphenol M cyanate prepolymer;
[0063] S3, adding the dispersion in step S1 to the bisphenol M cyanate prepolymer, stirring and reacting at 85° C. for 0.5 h to obtain bisphenol M cyanate resin.
[0064] Example 7
[0065] This embodiment provides a bisphenol M cyanate ester, including the following raw materials in parts by weight:
[0066] Bisphenol M cyanate resin monomer: 100 parts, epoxy resin: 15 parts, modified hydrotalcite in Example 1: 3 parts, copper acetylacetonate: 0.03 parts, nonylphenol: 0.1 parts.
[0067] The preparation method is as follows:
[0068] S1. Weigh copper acetylacetonate in parts by weight and add it to nonylphenol, and disperse it by high-speed shearing to obtain a dispersion;
[0069] S2, heating and stirring the bisphenol M cyanate monomer, epoxy resin and the modified hydrotalcite in Example 1, and stirring and reacting at 200° C. for 8 hours to obtain a bisphenol M cyanate prepolymer;
[0070] S3, adding the dispersion in step S1 to the bisphenol M cyanate prepolymer, stirring and reacting at 80° C. for 1 hour to obtain bisphenol M cyanate resin.
[0071] Comparative Example 1
[0072] Compared with Example 3, the only difference is:
[0073] A bisphenol M cyanate ester, comprising the following raw materials in parts by weight:
[0074] Bisphenol M cyanate resin monomer: 100 parts, epoxy resin: 15 parts, copper acetylacetonate: 0.03 parts, nonylphenol: 0.1 parts.
[0075] Comparative Example 2
[0076] Compared with Example 3, the only difference is:
[0077] 3 parts of the modified hydrotalcite in Example 1 were replaced by 1.5 parts of the modified hydrotalcite in Example 1.
[0078] Comparative Example 3
[0079] Compared with Example 3, the only difference is:
[0080] 3 parts of the modified hydrotalcite in Example 1 were replaced by 10.5 parts of the modified hydrotalcite in Example 1.
[0081] Comparative Example 4
[0082] Compared with Example 3, the only difference is:
[0083] A bisphenol M cyanate ester, comprising the following raw materials in parts by weight:
[0084] Bisphenol M cyanate resin monomer: 90 parts, epoxy resin: 15 parts, modified hydrotalcite in Example 1: 3 parts, copper acetylacetonate: 0.03 parts, nonylphenol: 0.1 parts.
[0085] Comparative Example 5
[0086] Compared with Example 3, the only difference is:
[0087] A bisphenol M cyanate ester, comprising the following raw materials in parts by weight:
[0088] Bisphenol M cyanate resin monomer: 100 parts, epoxy resin: 12 parts, modified hydrotalcite in Example 1: 3 parts, copper acetylacetonate: 0.01 parts, nonylphenol: 0.1 parts.
[0089] Comparative Example 6
[0090] Compared with Example 3, the only difference is:
[0091] The preparation method is as follows:
[0092] S2. Heat and stir the bisphenol M cyanate monomer, epoxy resin and the modified hydrotalcite in Example 1, and react them at 130° C. for 10 hours to obtain a bisphenol M cyanate prepolymer.
[0093] Comparative Example 7
[0094] Compared with Example 3, the only difference is:
[0095] S3, adding the dispersion in step S1 to the bisphenol M cyanate prepolymer, stirring and reacting at 75° C. for 0.5 h to obtain bisphenol M cyanate resin.
[0096] The following performance tests were performed on Examples 3 to 7 and Comparative Examples 1 to 7:
[0097] 1. Mechanical properties test: The test was conducted using the 5982 electronic universal material testing machine from Instron, USA, in accordance with GB / T2567-2008. The tensile specimen gauge length was 50mm, the thickness was 4mm, the fixture span was 120mm, and the loading speed was 2mm / min; the bending specimen size was 80mm×15mm×4mm, and the loading speed was 2mm / min;
[0098] 2. Hygroscopicity test: The test is conducted by boiling water at 100°C, and the sample size is 40mm×20mm×4mm;
[0099] 3. Dielectric property test: The test was conducted using the 8722ES microwave vector network analyzer from Hewlett-Packard Company of the United States using the resonant cavity method in accordance with GB / T 5597-1999. The test frequency was 7-18 GHz and the sample size was Φ61 mm × 4.8 mm.
[0100] The above test results are shown in Table 1:
[0101] Table 1
[0102]
[0103]
[0104] As can be seen from Table 1, compared with the bisphenol M cyanate resin obtained in Comparative Examples 1-7, the bisphenol M cyanate resin prepared in Examples 3-7 has excellent mechanical properties, hygroscopicity and dielectric properties. It can be seen that the raw material composition, ratio and process parameters of the preparation of bisphenol M cyanate resin will affect the performance of bisphenol M cyanate. In summary, the preparation method of the bisphenol M cyanate resin provided by the present invention is simple, low-cost, and suitable for large-scale industrial production.
[0105] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0106] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A bisphenol M cyanate, characterized in that: By weight, it includes the following raw materials: Bisphenol M cyanate resin monomer: 100 parts; Thermosetting resin: 15-20 parts; Modified hydrotalcite: 3-8 parts; Catalyst: 0.03-0.05 parts; Accelerator: 0.1-0.15 parts.
2. A bisphenol M cyanate according to claim 1, characterized in that: The preparation steps of the modified hydrotalcite are as follows: POSS was added to tetrahydrofuran, stirred, and hydrotalcite was added, and ultrasonic dispersion was performed for 1-1.5 hours. The temperature was controlled at 75-80°C, and reflux reaction was performed for 12-14 hours under nitrogen atmosphere. After the reaction was completed, the reaction was cooled to room temperature, filtered, washed, and dried to obtain modified hydrotalcite.
3. A bisphenol M cyanate according to claim 2, characterized in that: The usage ratio of POSS, tetrahydrofuran and hydrotalcite is 0.50-0.55 g:100 mL:0.10-0.12 g.
4. A bisphenol M cyanate according to claim 2, characterized in that: The particle size of the hydrotalcite is 30-60 μm.
5. A bisphenol M cyanate according to claim 1, characterized in that: The thermosetting resin is at least one of epoxy resin, bismaleimide resin and benzoxazine resin.
6. A bisphenol M cyanate according to claim 1, characterized in that: The catalyst is at least one of octanoic acid metal salt, acetylacetonate metal salt and dibutyl dilaurate metal salt.
7. A bisphenol M cyanate according to claim 1, characterized in that: The accelerator is one of nonylphenol, phenol, resorcinol and o-cresol.
8. The method for preparing bisphenol M cyanate according to claim 1, characterized in that: The following steps are involved: S1, weighing by weight, adding the catalyst to the accelerator, and dispersing by high-speed shearing to obtain a dispersion; S2, heating and stirring the bisphenol M cyanate monomer, the thermosetting resin and the modified hydrotalcite to obtain a bisphenol M cyanate prepolymer; S3, adding the dispersion in step S1 to the bisphenol M cyanate prepolymer, stirring and reacting to obtain bisphenol M cyanate resin.
9. The method for preparing bisphenol M cyanate according to claim 8, characterized in that: The stirring reaction temperature in S2 is 150-200°C, and the stirring reaction time is 8-10h.
10. The method for preparing bisphenol M cyanate according to claim 8, characterized in that: The stirring reaction temperature in S3 is 80-85°C, and the stirring reaction time is 0.5-1h.